Perencanaan Drainase Saluran Terbuka Pada Area Tambang Komoditas Tanah Liat Kabupaten Trenggalek - Muhammad Dani Dhaifullah; Tuhu Agung Rachmanto (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
One of the important aspects in mining activities is the drainage system. A good drainage system can prevent flooding, erosion, landslides, and water pollution caused by mining. The drainage system applied in the clay mining site consists of making drainage channels at the bottom of the mining benches. This is intended to capture the mine runoff water. The mine floor is sloped towards the drainage channel. Data collection is carried out, which includes data on location, area, and slope of the mining area, rainfall, runoff coefficient, and then calculations are performed using the Manning equation to obtain the channel dimensions. The planned open channel dimensions have a channel base width = 0.908 m, flow depth = 0.79 m, wet cross-sectional area = 1.07 m, wet perimeter = 1.943 m, hydraulic radius = 0.39 m, water surface width = 1.824 m, and freeboard = 0.197 m. The construction of the drainage channel is intended so that the water on the mine floor can flow directly to the drainage channel, thus not disturbing the mining activities